Histone Deacetylase 6 Regulates the Activation of M1 Macrophages by the Glycolytic Pathway During Acute Liver Failure - Wang Y (Dove Medical Press, 2021)
Yao Wang,* Xun Li,* Qian Chen, Fangzhou Jiao, Chunxia Shi, Maohua Pei, Luwen Wang, Zuojiong Gong Department of Infectious Diseases, Renmin Hospital of Wuhan University, Wuhan, 430060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zuojiong Gong; Luwen WangDepartment of Infectious Diseases, Renmin Hospital of Wuhan University, 238 Jiefang Road, Wuhan, 430060, People’s Republic of ChinaEmail zjgong@163.com; wangluw8253@163.comBackground: The glycolysis pathway of M1 macrophages is a key factor affecting the inflammatory response. The aim of this article is to investigate the role of histone deacetylase 6 (HDAC6) in the M1 macrophage glycolysis pathway during acute liver failure (ALF).Methodology: Targeted metabolomics for quantitative analysis of energy metabolites technology was used to detect the characteristics of energy metabolism for 8 ALF patients and 8 normal volunteers. The ALF mice model was intervened with HDAC6 inhibitor ACY-1215. iTRAQ/TMT quantitative proteomics was used to detect protein expression in livers in different mice groups. The liver function, energy metabolites, M1 macrophages, cytokines, and pathological structure, DDX3X, NLRP3 and DNMT1 in liver tissue were detected. The changes of the above molecules were verified in cell groups.Results: ALF patients and mice have significant energy metabolism disorders, accompanied by activation of M1 macrophages. After the intervention of ACY-1215, the activated M1 macrophages and cytokines levels in the mouse liver were reduced. The levels of IDH1, MDH1, and ATP were significantly increased. The expression of DDX3X increased, while the expression of NLRP3 and DNMT1 decreased. ACY-1215 could reduce the model cell apoptosis level and inflammatory response, and improve energy metabolism. It could also promote the expression of DDX3X, and inhibit the expression of NLRP3 and DNMT1.Conclusion: ACY-1215 could inhibit the activation of M1 macrophages by improving the glycolytic pathway through regulating DNMT1 and DDX3X/NLRP3 signals to alleviate ALF.Keywords: HDAC6, M1 macrophage, metabolic reprogramming, acute liver failure